Análise da difusão da emissão de certificações ISO 14001 nos países do continente americano - Hikichi, Suzana Eda (2016)
The ISO 14001 standard has been showing increasing importance for environmental management in organizations worldwide. To study and predict the behavior of the number of certifications in coming years is a strategy for planning and organizational management. The Americas is an important region in relation to the expansion of ISO 14001. However few studies related to the dissemination of the standard were carried out with the focus on the continent. Accordingly, this work aimed to characterize the diffusion of ISO 14001 standard in the countries and sectors in the Americas and adjust predictive models for the number of certifications. At the country level, the study was conducted with the number data of the ISO 14001 certificate in the 13 countries with the largest number of certifications between the years of 1996 to 2014. The ISO 14001 analysis was carried out in the countries through the evolution curves of the ISO 14001. The behavior of the standard at level of sectors was analyzed using data from the years of 1999 to 2014. The relationship between the number of ISO 14001 and ISO 9001 certifications for countries and sectors was evaluated by graphical analysis. In adjusting of the forecast models were applied the Box & Jenkins methodology for the annual series data from 13 countries. The results of the characterization showed that the diffusion is heterogeneously on the continent. The interest of organizations to certify varies between countries depending on internal factors. At the sector level, the certifications appear to be distributed among various sectors in the countries. The disparity between the number of ISO 14001 certifications in relation to ISO 9001 is being reduced over time in countries and sectors. The ARIMA models adjusted to the ISO 14001 series showed a growth trend in the number of certifications in the Americas and in Brazil, Colombia, United States and Mexico. Chile and Argentina have downward trend in the number of new certificates. These results suggest that countries that have conditions to implement the ISO 14001 should remain interested in coming years. The information obtained in this work can be useful to guide the planning strategies of certification bodies and business management.